Reduced graphene oxide / high-entropy alloy reinforced aluminum alloy bar and preparation method thereof
Nanoreductive graphene oxide/high entropy alloy particles were prepared by mechanical ball milling and hot pressing sintered with the aluminum alloy matrix, which solved the problem of surface quality and poor mechanical properties during the preparation of aluminum alloy composite materials, and achieved higher density and mechanical properties.
Patent Information
- Application Number
- CN202510446224.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-10
- Publication Date
- 2025-06-20
- Estimated Expiration
- 2045-04-10
AI Technical Summary
In the existing preparation methods of aluminum alloy composite materials, the surface wrinkle, peeling and low density are caused by cold pressing, as well as poor toughness and fatigue resistance caused by alumina reinforced particles, and the Al4C3 brittle phase is formed during high-temperature extrusion between the aluminum matrix and reduced graphene oxide, resulting in poor mechanical properties.
The high-entropy alloy is loaded on reduced graphene oxide by mechanical ball milling to form nanoreduced graphene oxide/high-entropy alloy particles. This is used as the reinforced particles and the aluminum alloy matrix to undergo hot pressing sintering and extrusion by powder metallurgy to obtain reduced graphene oxide/high-entropy alloy reinforced aluminum alloy rod material.
The density and mechanical properties of aluminum alloy rods are improved, microscopic defects are reduced, and the formation of Al4C3 brittle phase is avoided, thereby improving the comprehensive mechanical properties of aluminum alloy composite materials.
Smart Images

Figure CN120174228A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of the synthesis of aluminum alloys and nanomaterials, and particularly to reduced graphene oxide / high-entropy alloy reinforced aluminum alloy bars and a preparation method thereof. Background Art
[0002] Aluminum matrix composites, namely AMCs, are high-performance structural materials with high strength, high modulus, high stiffness and low cost. They are widely used in the automotive industry, aerospace, transportation and military fields, and have significant environmental and economic benefits. Powder metallurgy is one of the main methods for preparing aluminum matrix composites, which can ensure the uniformity and correctness of the material composition ratio, and the processed materials have high precision and consistency. However, in the past preparation process, the bars were extruded after cold pressing, which led to product quality problems such as easy surface wrinkling, peeling and low density of the materials.
[0003] When using reinforced particle-reinforced composites, the composition of the reinforced particle materials and the construction of the preparation process have attracted much attention. The influence of different types of reinforced particles on the material properties and the design of the forming process are the research focuses of aluminum matrix composites. The patent with the publication number CN116479274A discloses a preparation method of an aluminum alloy composite material obtained by adding nano-reduced graphene oxide / aluminum oxide particles to 6061 aluminum alloy. It is prepared by a hydrothermal method to obtain aluminum oxide loaded on the surface of nano-reduced graphene oxide at the same time, so as to obtain nano-reduced graphene oxide / aluminum oxide particles. However, this method has a long period and poor adhesion of aluminum oxide on the surface of nano-reduced graphene oxide, which increases the contact area between the aluminum matrix and reduced graphene oxide, making it easy for the two to react to form brittle phase Al4C3 during high-temperature extrusion, thus resulting in poor mechanical properties of the aluminum alloy composite material. In addition, the patent with the publication number CN118993713A discloses a toughened ceramic material and an additive manufacturing method. Although alumina, as a ceramic particle, has high hardness and high-temperature stability, it has problems of poor fracture toughness and weak fatigue resistance, thus resulting in poor mechanical properties of the prepared composite material. Summary of the Invention
[0004] The present invention provides a reduced graphene oxide / high-entropy alloy reinforced aluminum alloy bar and a preparation method thereof, effectively solving the quality problems of surface wrinkles, peeling, and low density of products caused by cold pressing and then extruding bars in the existing preparation methods of aluminum alloy composite materials, as well as the technical problems of poor toughness and fatigue resistance of aluminum alloy composite bars caused by using alumina as reinforcing particles and the generation of brittle phase Al4C3 when the aluminum matrix and reduced graphene oxide are extruded at high temperature, resulting in a decline in the mechanical properties of aluminum alloy composite materials. The present invention uses nano-reduced graphene oxide and high-entropy alloy as reinforcing particles, and mechanically composites the two reinforcing particles, greatly shortening the experimental period and increasing the adhesion rate of the high-entropy alloy on the surface of reduced graphene oxide. Then, the composite reinforcing particles are compounded with the aluminum alloy matrix, and one-step hot pressing and sintering are carried out before hot extrusion, thereby improving the density and mechanical properties of the aluminum alloy bar.
[0005] The first object of the present invention is to provide a preparation method of a reduced graphene oxide / high-entropy alloy reinforced aluminum alloy bar, comprising the following steps: By mechanical ball milling method, in a protective atmosphere, the high-entropy alloy is loaded on the reduced graphene oxide to obtain reduced graphene oxide / high-entropy alloy particles; the high-entropy alloy is composed of Al, Fe, Ni, Cr, and Co with a weight ratio of 0.5:1:1:1:1.
[0006] Using the reduced graphene oxide / high-entropy alloy particles as reinforcing particles and aluminum alloy powder as the matrix, through powder metallurgy method, hot pressing and sintering, and extrusion, a reduced graphene oxide / high-entropy alloy reinforced aluminum alloy bar is obtained; the mass of the reduced graphene oxide / high-entropy alloy particles is 0.1% - 0.3% of the mass of the aluminum alloy powder.
[0007] As a preferred embodiment, the mass ratio of the reduced graphene oxide to the high-entropy alloy is 1:0.8 - 1.2.
[0008] As a preferred embodiment, during hot pressing and sintering, the temperature is raised to 420°C - 450°C, the pressure is raised to 10MPa - 15MPa, and hot pressing and sintering are carried out for 60min - 70min.
[0009] As a preferred embodiment, stainless steel ball milling beads with diameters of 5mm, 8mm, and 10mm and a mass ratio of 3:2:1 are used, and at a rotation speed of 400r / min - 450r / min and a ball-to-material ratio of 10 - 20:1, the high-entropy alloy and reduced graphene oxide are ball milled for 4h - 6h.
[0010] As a preferred embodiment, during ball milling, n-heptane with a mass of 1% - 3% of the total mass of the reduced graphene oxide and high-entropy alloy is added, and ball milling is paused for 10min every 1h.
[0011] As a preferred embodiment, before hot pressing and sintering, the reduced graphene oxide / high-entropy alloy particles are mixed with aluminum alloy powder and ball milled for 8 h to 10 h at a rotation speed of 200 rpm to 240 rpm and a ball-to-material ratio of 5 to 6:1.
[0012] As a preferred embodiment, a preform is obtained after hot pressing and sintering. The preform is placed in an extrusion die, heated to 450 °C to 500 °C, held for 30 min to 40 min, and then extruded.
[0013] The second object of the present invention is to provide a reduced graphene oxide / high-entropy alloy reinforced aluminum alloy rod prepared by the above preparation method.
[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention provides a preparation method for reduced graphene oxide / high-entropy alloy reinforced aluminum alloy rods. In the present invention, nano-reduced graphene oxide and high-entropy alloy are ball milled in a protective atmosphere. Through the impact and grinding effects generated by the mechanical ball milling method, a high-strength mechanical adhesion is formed between the nano-reduced graphene oxide and the high-entropy alloy, thereby improving the adhesion of the high-entropy alloy on the surface of the nano-reduced graphene oxide to obtain nano-reduced graphene oxide / high-entropy alloy particles. In a powder metallurgy manner, the nano-reduced graphene oxide / high-entropy alloy particles are hot pressed and sintered with aluminum alloy powder and then extruded to obtain a reduced graphene oxide / high-entropy alloy reinforced aluminum alloy rod. Through hot pressing and pre-sintering, a preliminary metallurgical effect is formed on the surface of the metal blank, thereby improving the quality problems of product wrinkles, skinning, and low density during the subsequent hot extrusion process. The high-entropy alloy formed by Al, Fe, Ni, Cr, and Co used in the present invention has excellent strength, hardness, toughness, and fatigue resistance. The high-entropy alloy and nano-reduced graphene oxide are used as reinforcing particles to be compounded with aluminum alloy and then hot extruded, further improving the comprehensive mechanical properties of the aluminum alloy rod and reducing microdefects, thereby effectively avoiding the technical problem that the mechanical properties of the aluminum alloy composite are poor due to the formation of brittle Al4C3 phase during the high-temperature extrusion of the aluminum matrix and reduced graphene oxide. Description of the Drawings
[0015] Figure 1 It is a SEM image of the reduced graphene oxide / high-entropy alloy particles prepared in Example 1 of the present invention, and HEA represents high-entropy alloy.
[0016] Figure 2 It is the transverse SEM microstructure of the aluminum alloy rod prepared by the present invention. Among them, Figure (a) is Comparative Example 1, Figure (b) is Example 1, Figure (c) is Example 2, and Figure (d) is Example 3.
[0017] Figure 3SEM microstructures of the fracture surfaces of the tensile specimens of the aluminum alloy bars prepared according to the present invention, where (a) is Comparative Example 1, (b) is Example 1, (c) is Example 2, (d) is Example 3, (e) is Comparative Example 3, and (f) is Comparative Example 2.
[0018] Figure 4 XRD patterns of the aluminum alloy bars prepared in Examples 1 to 3 and Comparative Examples 1 to 3 of the present invention.
[0019] Figure 5 Vickers hardness curves of the aluminum alloy bars prepared in Comparative Examples 1 to 3 and Examples 1 to 3 of the present invention.
[0020] Figure 6 True stress-strain curves of the tensile tests of the aluminum alloy bars prepared in Comparative Example 1 and Examples 1 to 3 of the present invention.
[0021] Figure 7 Bar charts of the tensile strength, yield strength, and elongation of the aluminum alloy bars prepared in Comparative Examples 1 to 3 and Examples 1 to 3 of the present invention. Detailed Description of the Invention
[0022] In order to enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific examples, but the examples given are not intended to limit the present invention. The following test methods and detection methods are all conventional methods unless otherwise specified; the reagents and raw materials are all commercially available unless otherwise specified.
[0023] Regarding the following technical problems existing in the existing aluminum matrix composites: First, the preparation process of the aluminum matrix composites is to extrude the bars after cold pressing, which results in product quality problems such as easy surface wrinkles, peeling, and low density of the materials; Second, when preparing the reinforcing particles of the aluminum matrix composites, alumina is prepared by hydrothermal method and loaded on the surface of nano-reduced graphene oxide. This method has a long period and poor adhesion of alumina on the surface of nano-reduced graphene oxide, thereby increasing the contact area between the aluminum matrix and reduced graphene oxide, making it easy for the two to react to form brittle Al4C3 phase during high-temperature extrusion, thus resulting in poor mechanical properties of the aluminum alloy composites; Third, although alumina has high hardness, its toughness and fatigue resistance are relatively weak. Based on the above technical problems, the present invention provides reduced graphene oxide / high-entropy alloy reinforced aluminum alloy bars and their preparation methods.
[0024] The technical solutions of the present invention will be described in detail below.
[0025] The present invention first provides a method for preparing reduced graphene oxide / high-entropy alloy reinforced aluminum alloy bars, comprising the following steps: By means of mechanical ball milling method, in a protective atmosphere, a high-entropy alloy is loaded on reduced graphene oxide to obtain reduced graphene oxide / high-entropy alloy particles; the high-entropy alloy is composed of Al, Fe, Ni, Cr and Co with a weight ratio of 0.5:1:1:1:1.
[0026] Using the reduced graphene oxide / high-entropy alloy particles as reinforcing particles and aluminum alloy powder as the matrix, through powder metallurgy method, hot press sintering and extrusion, a reduced graphene oxide / high-entropy alloy reinforced aluminum alloy rod is obtained.
[0027] In the above technical solution, through the impact and grinding effects generated by the mechanical ball milling method, a high-strength mechanical adhesion is formed between the reduced graphene oxide and the high-entropy alloy, thereby improving the adhesion of the high-entropy alloy on the surface of the reduced graphene oxide. Through hot press pre-sintering, a preliminary metallurgical effect is formed on the surface of the metal blank, thus improving the quality problems of product wrinkles, peeling and low density during the subsequent hot extrusion process. The high-entropy alloy formed by Al, Fe, Ni, Cr and Co and reduced graphene oxide as reinforcing particles are compounded with aluminum alloy and then hot extruded, further improving the comprehensive mechanical properties of the aluminum alloy rod and reducing the micro defects, thereby effectively avoiding the technical problem that the mechanical properties of the aluminum alloy composite are poor due to the formation of brittle phase Al4C3 when the aluminum matrix and reduced graphene oxide are hot extruded at high temperature.
[0028] As a preferred implementation manner, the mass ratio of the reduced graphene oxide to the high-entropy alloy is 1:0.8~1.2. If the proportion of the high-entropy alloy used is lower than 0.8 here, that is, the amount of the high-entropy alloy used is less, it will lead to a decrease in the loading rate of the high-entropy alloy on the reduced graphene oxide and a decline in its strengthening effect; if the proportion of the high-entropy alloy used is greater than 1.2 here, that is, the amount of the high-entropy alloy used is too much, it will lead to graphene agglomeration, thus reducing the mechanical properties of the aluminum alloy rod.
[0029] It should be noted that the high-entropy alloy used in the present invention is composed of Al, Fe, Ni, Cr and Co with a weight ratio of 0.5:1:1:1:1, and the high-entropy alloy is purchased from Aero Engine New Materials Technology Co., Ltd.
[0030] In order to improve the mechanical strength of the aluminum alloy matrix, the mass of the reduced graphene oxide / high-entropy alloy particles is 0.1%~0.3% of the mass of the aluminum alloy powder. If the mass percentage of the reduced graphene oxide / high-entropy alloy particles is less than 0.1% here, the improvement of the mechanical properties will not be obvious and the strengthening effect will be small; if the mass percentage of the reduced graphene oxide / high-entropy alloy particles is greater than 0.3% here, it will lead to local agglomeration, thus reducing the mechanical properties of the aluminum alloy rod.
[0031] In order to further improve the mechanical strength of the aluminum alloy bar and facilitate the placement of the mixture of the high-entropy alloy and reduced graphene oxide into the extrusion die, during hot press sintering, the temperature is raised to 420°C - 450°C, the pressure is raised to 10 MPa - 15 MPa, and hot press sintering is carried out for 60 min - 70 min.
[0032] In order to improve the adhesion of the high-entropy alloy on the surface of reduced graphene oxide, stainless steel ball milling beads with diameters of 5 mm, 8 mm, and 10 mm and a mass ratio of 3:2:1 are used. At a rotation speed of 400 r / min - 450 r / min and a ball-to-material ratio of 10 - 20:1, the high-entropy alloy and reduced graphene oxide are ball milled for 4 h - 6 h.
[0033] In order to prevent cold welding caused by excessive temperature during the operation of the ball mill and improve the ball milling effect, during ball milling, n-heptane accounting for 1% - 3% of the total mass of reduced graphene oxide and the high-entropy alloy is added, and the ball milling is paused for 10 min every 1 h.
[0034] In order to improve the dispersion uniformity of the reduced graphene oxide / high-entropy alloy particles in the aluminum alloy matrix, before hot press sintering, the reduced graphene oxide / high-entropy alloy particles are mixed with aluminum alloy powder, and ball milled at a rotation speed of 200 rpm - 240 rpm and a ball-to-material ratio of 5 - 6:1 for 8 h - 10 h.
[0035] In order to prepare an aluminum alloy bar with excellent mechanical properties, a preform is obtained after hot press sintering. The preform is placed in an extrusion die, heated to 450°C - 500°C, held for 30 min - 40 min, and then extruded.
[0036] The following specifically describes the content of the present invention through the following examples and comparative examples.
[0037] Example 1 A preparation method of reduced graphene oxide / high-entropy alloy reinforced aluminum alloy bar, comprising the following steps: S1, preparing graphene oxide by the improved Hummers method: dispersing graphene oxide in deionized water to form a graphene oxide suspension with a concentration of 0.04 g / mL, adding the graphene oxide suspension into a hydrothermal reaction kettle with a polytetrafluoroethylene lining, sealing it, and carrying out hydrothermal reaction at 180°C for 8 h to obtain reduced graphene oxide, denoted as RGO.
[0038] S2, Weigh 1 g of high-entropy alloy and 1 g of RGO respectively. Using three types of stainless steel ball milling beads with a mass ratio of 3:2:1, diameters of 5 mm, 8 mm, and 10 mm, in a high-energy planetary ball mill with a rotation speed of 450 r / min and a ball-to-material ratio of 10:1, ball mill the high-entropy alloy and RGO for 5 h for mechanical adhesion. During the ball milling process, introduce argon gas for protection to prevent the high-entropy alloy from oxidizing during the mechanical ball milling process. Then add 1% of the total mass of the high-entropy alloy and RGO, namely n-heptane, as a process inhibitor to prevent overheating during equipment operation and resulting in cold welding. The ball mill stops for 10 min every 1 h of operation. After the ball milling is completed, perform centrifugal cleaning with absolute ethanol and dry it to obtain reduced graphene oxide / high-entropy alloy particles.
[0039] S3, Based on the mass of 6061 aluminum alloy powder, add 0.1 wt% of reduced graphene oxide / high-entropy alloy particles to the 6061 aluminum alloy powder. Using grinding balls with a mass ratio of 1:3:1, diameters of 10 mm, 8 mm, and 4 mm, and a total mass of 600 g, in a high-energy ball mill with a rotation speed of 200 r / min and a ball-to-material ratio of 5:1, ball mill for 10 h. The total mass of the 6061 aluminum alloy powder and the reduced graphene oxide / high-entropy alloy particle powder is 120 g to obtain aluminum-based composite powder.
[0040] S4, Load the aluminum-based composite powder into a hot pressing and sintering mold, apply a pressure of 15 MPa and heat to 420 °C for hot pressing and sintering for 60 min, and cool with the furnace to obtain a preform.
[0041] S5, Place the preform in an extrusion mold, heat to 500 °C and keep it warm for 30 min, and then extrude with an extrusion ratio of 1:16 to obtain a reduced graphene oxide / high-entropy alloy reinforced aluminum alloy bar.
[0042] Example 2 A method for preparing a reduced graphene oxide / high-entropy alloy reinforced aluminum alloy bar, comprising the following steps: S1, Prepare graphene oxide by the improved Hummers method: Disperse graphene oxide in deionized water to form a graphene oxide suspension with a concentration of 0.04 g / mL. Add the graphene oxide suspension to a hydrothermal reaction kettle with a polytetrafluoroethylene lining. After sealing, carry out a hydrothermal reaction at 180 °C for 8 h to obtain reduced graphene oxide, denoted as RGO.
[0043] S2. Weigh 1 g of high-entropy alloy and 1 g of RGO respectively. Use three kinds of stainless steel ball milling beads with diameters of 5 mm, 8 mm, and 10 mm and a mass ratio of 3:2:1. In a high-energy planetary ball mill with a rotation speed of 450 r / min and a ball-to-material ratio of 10:1, ball mill the high-entropy alloy and RGO for 5 h for mechanical adhesion. During the ball milling process, introduce argon gas for protection to prevent the high-entropy alloy from oxidizing during the mechanical ball milling process. Then add 1% of the process inhibitor n-heptane based on the total mass of the high-entropy alloy and RGO to prevent overheating during equipment operation and resulting in cold welding. The ball mill stops for 10 min every 1 h of operation. After ball milling, perform centrifugal cleaning with absolute ethanol and dry to obtain reduced graphene oxide / high-entropy alloy particles.
[0044] S3. Based on the mass of 6061 aluminum alloy powder, add 0.2 wt% of reduced graphene oxide / high-entropy alloy particles to the 6061 aluminum alloy powder. Use grinding balls with a mass ratio of 1:3:1, diameters of 10 mm, 8 mm, and 4 mm, and a total mass of 600 g. In a high-energy ball mill with a rotation speed of 200 r / min and a ball-to-material ratio of 5:1, ball mill for 10 h. The total mass of the 6061 aluminum alloy powder and the reduced graphene oxide / high-entropy alloy particle powder is 120 g to obtain aluminum-based composite powder.
[0045] S4. Load the aluminum-based composite powder into a hot pressing and sintering mold, apply a pressure of 15 MPa and heat to 420 °C for hot pressing and sintering for 60 min, and cool with the furnace to obtain a preform.
[0046] S5. Place the preform in an extrusion mold, heat to 500 °C and keep it warm for 30 min, and then extrude with an extrusion ratio of 1:16 to obtain a reduced graphene oxide / high-entropy alloy reinforced aluminum alloy rod.
[0047] Example 3 A preparation method of a reduced graphene oxide / high-entropy alloy reinforced aluminum alloy rod, comprising the following steps: S1. Prepare graphene oxide by the improved Hummers method: Disperse graphene oxide in deionized water to form a graphene oxide suspension with a concentration of 0.04 g / mL. Add the graphene oxide suspension to a hydrothermal reaction kettle with a polytetrafluoroethylene lining. After sealing, carry out hydrothermal reaction at 180 °C for 8 h to obtain reduced graphene oxide, denoted as RGO.
[0048] S2, Weigh 1 g of high-entropy alloy and 1 g of RGO respectively. Using three types of stainless steel ball milling beads with a mass ratio of 3:2:1 and diameters of 5 mm, 8 mm, and 10 mm, in a high-energy planetary ball mill with a rotation speed of 450 r / min and a ball-to-material ratio of 10:1, ball mill the high-entropy alloy and RGO for 5 h for mechanical adhesion. During the ball milling process, introduce argon gas for protection to prevent the high-entropy alloy from oxidizing during the mechanical ball milling process. Then add n-heptane, a process inhibitor accounting for 1% of the total mass of the high-entropy alloy and RGO, to prevent overheating during equipment operation and resulting in cold welding. The ball mill stops for 10 min every 1 h of operation. After the ball milling is completed, perform centrifugal cleaning with anhydrous ethanol and dry to obtain reduced graphene oxide / high-entropy alloy particles.
[0049] S3, Based on the mass of 6061 aluminum alloy powder, add 0.3 wt% of reduced graphene oxide / high-entropy alloy particles to the 6061 aluminum alloy powder. Using grinding balls with a mass ratio of 1:3:1, diameters of 10 mm, 8 mm, and 4 mm, and a total mass of 600 g, in a high-energy ball mill with a rotation speed of 200 r / min and a ball-to-material ratio of 5:1, ball mill for 10 h. The total mass of the 6061 aluminum alloy powder and the reduced graphene oxide / high-entropy alloy particle powder is 120 g to obtain aluminum-based composite powder.
[0050] S4, Load the aluminum-based composite powder into a hot pressing and sintering mold, apply a pressure of 15 MPa, heat to 420 °C, and perform hot pressing and sintering for 60 min, and cool with the furnace to obtain a preform.
[0051] S5, Place the preform in an extrusion mold, heat to 500 °C and keep it warm for 30 min, and then extrude with an extrusion ratio of 1:16 to obtain a reduced graphene oxide / high-entropy alloy reinforced aluminum alloy bar.
[0052] To further illustrate the effects of the present invention, the present invention also sets up a comparative example as follows: Comparative Example 1 Compared with Example 1, the difference is that reduced graphene oxide / high-entropy alloy particles are not added to the aluminum alloy bar, and only pure 6061 aluminum alloy is used to prepare the aluminum alloy bar.
[0053] A method for preparing an aluminum alloy bar, comprising the following steps: S1, Using pure 6061 aluminum powder particles, with grinding balls having a mass ratio of 1:3:1, diameters of 10 mm, 8 mm, and 4 mm, and a total mass of 600 g, in a high-energy ball mill with a rotation speed of 200 r / min and a ball-to-material ratio of 5:1, ball mill for 10 h. The mass of the 6061 aluminum alloy matrix is 120 g to obtain aluminum-based powder.
[0054] S2. Load the aluminum-based powder into a hot-pressing sintering mold, apply a pressure of 15 MPa, heat to 420 °C, and perform hot-pressing sintering for 60 min, then cool with the furnace to obtain a preform.
[0055] S3. Place the preform in an extrusion mold, heat to 500 °C and hold for 30 min, then extrude with an extrusion ratio of 1:16 to obtain an aluminum alloy bar.
[0056] Comparative Example 2 Compared with Example 1, the difference is that reduced graphene oxide is not added to the aluminum alloy bar, and only the high-entropy alloy and 6061 aluminum alloy are used to prepare the aluminum alloy bar.
[0057] A preparation method of a high-entropy alloy-reinforced aluminum alloy bar, comprising the following steps: S1. Based on the mass of the 6061 aluminum alloy powder, add 0.1 wt% of the high-entropy alloy to the 6061 aluminum alloy powder. Use grinding balls with a mass ratio of 1:3:1, diameters of 10 mm, 8 mm, and 4 mm, and a total mass of 600 g. In a high-energy ball mill with a rotation speed of 200 r / min and a ball-to-material ratio of 5:1, ball-mill the high-entropy alloy and 6061 aluminum alloy powder for 10 h. The total mass of the 6061 aluminum alloy powder and the high-entropy alloy particle powder is 120 g to obtain an aluminum-based composite powder.
[0058] S3. Load the aluminum-based composite powder into a hot-pressing sintering mold, apply a pressure of 15 MPa, heat to 420 °C, and perform hot-pressing sintering for 60 min, then cool with the furnace to obtain a preform.
[0059] S4. Place the preform in an extrusion mold, heat to 500 °C and hold for 30 min, then extrude with an extrusion ratio of 1:16 to obtain a high-entropy alloy-reinforced aluminum alloy bar.
[0060] Comparative Example 3 Compared with Example 1, the difference is that the high-entropy alloy is not added to the aluminum alloy bar, and only reduced graphene oxide and 6061 aluminum alloy are used to prepare the aluminum alloy bar.
[0061] A preparation method of a reduced graphene oxide-reinforced aluminum alloy bar, comprising the following steps: S1. Prepare graphene oxide by the improved Hummers method: Disperse graphene oxide in deionized water to form a graphene oxide suspension with a concentration of 0.04 g / mL. Add the graphene oxide suspension to a hydrothermal reaction kettle with a polytetrafluoroethylene lining. After sealing, perform hydrothermal reaction at 180 °C for 8 h to obtain reduced graphene oxide, denoted as RGO.
[0062] S2. Based on the mass of the 6061 aluminum alloy matrix, 0.1 wt% reduced graphene oxide is added to the 6061 aluminum alloy matrix. Grinding balls with a mass ratio of 1:3:1, diameters of 10 mm, 8 mm, and 4 mm, and a total mass of 600 g are used. Ball milling is carried out for 10 h at a rotation speed of 200 r / min and a ball-to-material ratio of 5:1. The total mass of the 6061 aluminum alloy matrix and reduced graphene oxide is 120 g to obtain aluminum-based composite powder.
[0063] S3. The aluminum-based composite powder is loaded into a hot pressing and sintering mold, pressurized at 15 MPa, heated to 420 °C, and hot pressed and sintered for 60 min, and then cooled in the furnace to obtain a preform.
[0064] S4. The preform is placed in an extrusion mold, heated to 500 °C and kept warm for 30 min, and then extruded at an extrusion ratio of 1:16 to obtain a reduced graphene oxide-reinforced aluminum alloy rod.
[0065] The properties of the aluminum alloy rods provided in Examples 1 to 3 and Comparative Examples 1 to 3 above are respectively detected, and the results are as follows.
[0066] Figure 1 This is the SEM image of the reduced graphene oxide / high-entropy alloy particles prepared in Example 1 of the present invention. From Figure 1 it can be seen that the high-entropy alloy is significantly attached to the surface of the reduced graphene oxide, which proves that two reinforcing particles, high-entropy alloy and reduced graphene oxide, are introduced into the 6061 aluminum alloy matrix in the present invention.
[0067] Figure 2 This is the transverse SEM microstructure of the aluminum alloy rod prepared in the present invention. Among them, Figure (a) is Comparative Example 1, Figure (b) is Example 1, Figure (c) is Example 2, and Figure (d) is Example 3. From Figure 2 it can be seen that in Examples 1 to 3, the reduced graphene oxide / high-entropy alloy is used as the reinforcing particle and is closely attached to the 6061 aluminum alloy matrix, and there are no obvious voids and defects in the material.
[0068] Figure 3 This is the SEM microstructure of the fracture surface morphology of the tensile specimen of the aluminum alloy rod prepared in the present invention. Among them, Figure (a) is Comparative Example 1, Figure (b) is Example 1, Figure (c) is Example 2, Figure (d) is Example 3, Figure (e) is Comparative Example 3, and Figure (f) is Comparative Example 2. From Figure 3It can be seen that the dimples of the fracture surfaces of the aluminum alloy bars with reduced graphene oxide / high entropy alloy added in Examples 1 to 3 are smaller. In Comparative Example 1, no reinforcing particles were added, and in Comparative Example 2, only high entropy alloy was used as the reinforcing particle. It was observed that the inhomogeneous deformation caused by the strength difference between HEA and the aluminum alloy matrix promoted the growth and coalescence of micropores during the tensile process. In Comparative Example 3, only reduced graphene oxide was used as the reinforcing particle. Due to the agglomeration of graphene, the dimples were larger, resulting in a decrease in the mechanical properties of the aluminum alloy bars.
[0069] Figure 4 This is the XRD analysis result of the aluminum alloy bars prepared by the present invention. From Figure 4 It can be seen that: after adding reduced graphene oxide / high entropy alloy particles to the 6061 aluminum alloy matrix of the present invention, no Al4C3 peak appears, that is, there is no brittle phase that will cause poor mechanical properties in the aluminum alloy bars prepared by the present invention. Therefore, the comprehensive mechanical properties of the aluminum alloy bars prepared by the present invention are better.
[0070] Figure 5 This is the average Vickers hardness curve graph of the aluminum alloy bars prepared in Comparative Examples 1 to 3 and Examples 1 to 3 of the present invention. From Figure 5 It can be seen that: compared with Comparative Example 1, after adding 0.1% of reduced graphene oxide / high entropy alloy particles by mass of the 6061 aluminum alloy matrix in Example 1, the average Vickers hardness of the aluminum alloy bars increased by 45.7%. Compared with Comparative Example 2, the average Vickers hardness of the aluminum alloy bars in Example 1 increased by 9.3%. Compared with Comparative Example 3, the average Vickers hardness of the aluminum alloy bars in Example 1 increased by 58.4%.
[0071] Figure 6 This is the true stress-strain curve of the tensile test of the aluminum alloy bars prepared in Comparative Example 1, Comparative Example 3 and Examples 1 to 3 of the present invention. From Figure 6 It can be seen that: among them, in Example 1, when the addition amount of reduced graphene oxide / high entropy alloy was 0.1 wt.%, the comprehensive mechanical properties of the prepared aluminum alloy bars were the best.
[0072] Figure 7 This is the bar graph of the tensile strength, yield strength and elongation rate of the aluminum alloy bars prepared in Comparative Example 1 and Examples 1 to 3 of the present invention. From Figure 7 It can be seen that: among them, the comprehensive mechanical properties of the aluminum alloy bars prepared in Example 1 are the best, with the tensile strength increased by 36.2%, the yield strength increased by 46.5%, and the elongation rate increased by 2.56%.
[0073] Compared with the performance of the aluminum alloy bars prepared in the examples, the performance of the aluminum alloy bars obtained in the above Comparative Examples 1 to 3 is not good. The main reasons are as follows: In Comparative Example 1, the pure 6061 aluminum alloy bar has no reinforcing particles in the matrix, resulting in larger internal grains and no dislocation accumulation after hot extrusion. During the stretching process, the grain boundaries are prone to slip, resulting in reduced mechanical properties.
[0074] In Comparative Example 2, only high entropy alloys were added to the 6061 aluminum alloy matrix as reinforcing particles. Due to the local agglomeration of the high entropy alloy, the internal stress distribution in the matrix was uneven, making the material tend to be brittle, resulting in reduced mechanical properties of the aluminum alloy rod.
[0075] In Comparative Example 3, only reduced graphene oxide was added to the 6061 aluminum alloy matrix as reinforcing particles. Due to the local agglomeration of the reduced graphene oxide, the mechanical properties of the aluminum alloy rod were reduced.
[0076] In summary, the present invention attaches a high entropy alloy to the surface of reduced graphene oxide by mechanical ball milling, and hot presses and sinters the reduced graphene oxide / high entropy alloy particles and aluminum alloy powder in a powder metallurgical manner, and extrude to obtain reduced graphene oxide / high entropy alloy reinforced aluminum alloy rods. Preliminary metallurgical effects are formed on the surface of the metal blank by hot pressing pre-sintering, thereby improving the quality problems of product wrinkling, peeling, and low density during subsequent hot extrusion. High entropy alloys formed by Al, Fe, Ni, Cr, and Co and reduced graphene oxide are reinforced particles and aluminum alloy composites through hot extrusion, further improving the comprehensive mechanical properties of aluminum alloy rods and reducing micro defects, thereby solving the technical problem of poor mechanical properties of aluminum alloy rods.
[0077] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a reduced graphene oxide / high entropy alloy reinforced aluminum alloy bar, characterized in that: The following steps are involved: By mechanical ball milling in a protective atmosphere, a high entropy alloy is loaded on reduced graphene oxide to obtain reduced graphene oxide / high entropy alloy particles; the high entropy alloy is composed of Al, Fe, Ni, Cr and Co in a weight ratio of 0.5:1:1:1:1; The reduced graphene oxide / high entropy alloy particles are used as reinforced particles and the aluminum alloy powder is used as a matrix. The reduced graphene oxide / high entropy alloy reinforced aluminum alloy rods are obtained by powder metallurgy, hot pressing, sintering and extrusion. The mass of the reduced graphene oxide / high entropy alloy particles is 0.1% to 0.3% of the mass of the aluminum alloy powder.
2. The method for preparing the reduced graphene oxide / high entropy alloy reinforced aluminum alloy rod according to claim 1, characterized in that: The mass ratio of the reduced graphene oxide to the high entropy alloy is 1:0.8-1.
2.
3. The method for preparing the reduced graphene oxide / high entropy alloy reinforced aluminum alloy rod according to claim 1, characterized in that: During hot pressing sintering, the temperature is raised to 420°C~450°C, the pressure is raised to 10MPa~15MPa, and the hot pressing sintering is performed for 60min~70min.
4. The method for preparing the reduced graphene oxide / high entropy alloy reinforced aluminum alloy rod according to claim 1, characterized in that: The high entropy alloy and reduced graphene oxide are ball-milled for 4 h to 6 h at a rotation speed of 400 r / min to 450 r / min and a ball-to-material ratio of 10 to 20, using stainless steel ball milling beads with diameters of 5 mm, 8 mm and 10 mm and a mass ratio of 3:2:
1.
5. The method for preparing the reduced graphene oxide / high entropy alloy reinforced aluminum alloy rod according to claim 4, characterized in that: During ball milling, 1% to 3% of the total mass of reduced graphene oxide and high entropy alloy is added in n-heptane.
6. The method for preparing the reduced graphene oxide / high entropy alloy reinforced aluminum alloy rod according to claim 1, characterized in that: Before hot pressing and sintering, the reduced graphene oxide / high entropy alloy particles are mixed with aluminum alloy powder and ball milled for 8h to 10h at a rotation speed of 200rpm to 240rpm and a ball-to-material ratio of 5 to 6:
1.
7. The method for preparing reduced graphene oxide / high entropy alloy reinforced aluminum alloy rod according to claim 1, characterized in that: After hot pressing and sintering, a preform is obtained, and the preform is placed in an extrusion die, heated to 450° C. to 500° C., kept warm for 30 min to 40 min, and extruded.
8. A reduced graphene oxide / high entropy alloy reinforced aluminum alloy rod prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
High-entropy alloy particle-reinforced aluminum-based composite material and preparation method thereof
CN104862510A
Preparation method of high-entropy alloy reinforced aluminum-based composite material and product
CN114309625A
Preparation method for obtaining aluminum alloy composite material by adding nano reduced graphene oxide / aluminum oxide particles into 6061 aluminum alloy
CN116479274A
Graphene modified high-entropy alloy particle reinforced titanium-based composite material as well as preparation method and application thereof
CN119553137A
High-entropy alloy reinforced aluminum-based composite material and preparation method and application thereof
CN119571140A